You are on page 1of 7

Part # 2:

P 6-1:

1 𝑟0 3 3 𝑟0 1 𝑟0 3 3 𝑟0
𝑣𝑟 = 𝑈 cos 𝜃 [1 + ( ) − ( )] 𝑈 cos 𝜃 (1 + ( ) − ( ))
2 𝑟 2 𝑟 2 𝑟 2 𝑟
1 𝑟0 3 3 𝑟0
𝑣𝜃 = 𝑈 sin 𝜃 [−1 + ( ) + ( )] 𝑣𝑖 = 1 𝑟0 3 3 𝑟0
4 𝑟 4 𝑟 𝑈 sin 𝜃 (−1 + ( ) + ( ))
4 𝑟 4 𝑟
𝑣𝜑 = 0
[ 0 ]
From Table C.2: Spherical Coordinates (r, θ, φ):

𝜕𝑣𝑟 1 𝜕 𝑣𝜃 1 𝜕𝑣𝑟
𝑆𝑟𝑟 = 𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ( ) + ]
𝜕𝑟 2 𝜕𝑟 𝑟 𝑟 𝜕𝜃

1 𝜕𝑣𝜃 𝑣𝑟 1 1 𝜕𝑣𝜃 sin 𝜃 𝜕 𝑣𝜙


𝑆𝜃𝜃 = + 𝑆𝜃𝜙 = 𝑆𝜙𝜃 = [ + ( )]
𝑟 𝜕𝜃 𝑟 2 𝑟 sin 𝜃 𝜕𝜙 𝑟 𝜕𝜃 sin 𝜃

1 𝜕𝑣𝜙 𝑣𝑟 𝑣𝜃 cot 𝜃 1 1 𝜕𝑣𝑟 𝜕 𝑣𝜙


𝑆𝜙𝜙 = + + 𝑆𝜙𝑟 = 𝑆𝑟𝜙 = [ + 𝑟 ( )]
𝑟 sin 𝜃 𝜕𝜙 𝑟 𝑟 2 𝑟 sin 𝜃 𝜕𝜙 𝜕𝑟 𝑟

𝜕𝑣𝑟 𝜕 1 𝑟0 3 3 𝑟0 𝑈 cos 𝜃 3 𝑟0 4 3 𝑟0 2
𝑆𝑟𝑟 = = 𝑈 cos 𝜃 ( ( ) − ( )) = (− ( ) + ( ) )
𝜕𝑟 𝜕𝑟 2 𝑟 2 𝑟 𝑟0 2 𝑟 2 𝑟

𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟐 𝒓𝟎 𝟒
𝑺𝒓𝒓 = [( ) − ( ) ]
𝟐 𝒓𝟎 𝒓 𝒓

1 𝜕𝑣𝜃 𝑣𝑟 1 𝑟0 3 3 𝑟0 1 𝜕(sin 𝜃) 1 1 𝑟 0 3 3 𝑟0
𝑆𝜃𝜃 = + = 𝑈 [−1 + ( ) + ( )] + 𝑈 cos 𝜃 [1 + ( ) − ( )]
𝑟 𝜕𝜃 𝑟 4 𝑟 4 𝑟 𝑟 𝜕𝜃 𝑟 2 𝑟 2 𝑟
𝑈 cos 𝜃 1 𝑟0 3 3 𝑟0 1 𝑟0 3 3 𝑟0 𝑈 cos 𝜃 3 𝑟0 3 3 𝑟0
𝑆𝜃𝜃 = {[−1 + ( ) + ( )] + [1 + ( ) − ( )]} = [ ( ) − ( )]
𝑟 4 𝑟 4 𝑟 2 𝑟 2 𝑟 𝑟 4 𝑟 4 𝑟

𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝑺𝜽𝜽 = [( ) − ( ) ]
𝟒 𝒓𝟎 𝒓 𝒓

1 𝜕𝑣𝜙 𝑣𝑟 𝑣𝜃 cot 𝜃
𝑆𝜙𝜙 = + +
𝑟 sin 𝜃 𝜕𝜙 𝑟 𝑟

1 1 𝑟 0 3 3 𝑟0 1 cos 𝜃 1 𝑟0 3 3 𝑟0
𝑆𝜙𝜙 = 𝑈 cos 𝜃 [1 + ( ) − ( )] + {𝑈 sin 𝜃 [−1 + ( ) + ( )]}
𝑟 2 𝑟 2 𝑟 𝑟 sin 𝜃 4 𝑟 4 𝑟

1 1 𝑟0 3 3 𝑟0 1 𝑟0 3 3 𝑟0
𝑆𝜙𝜙 = 𝑈 cos 𝜃 {[1 + ( ) − ( )] + [−1 + ( ) + ( )]}
𝑟 2 𝑟 2 𝑟 4 𝑟 4 𝑟
1 3 𝑟0 3 𝑟0 3
𝑆𝜙𝜙 = 𝑈 cos 𝜃 {− ( ) + ( ) }
𝑟 4 𝑟 4 𝑟

𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝑺𝝓𝝓 = [( ) − ( ) ]
𝟒 𝒓𝟎 𝒓 𝒓

3 𝑈 cos 𝜃 𝑟0 2 𝑟0 4 3 𝑈 cos 𝜃 𝑟0 4 𝑟0 2 3 𝑈 cos 𝜃 𝑟0 4 𝑟0 2


𝑆𝑟𝑟 + 𝑆𝜃𝜃 + 𝑆𝜙𝜙 = (( ) − ( ) ) + [( ) − ( ) ] + {( ) − ( ) }
2 𝑟0 𝑟 𝑟 4 𝑟0 𝑟 𝑟 4 𝑟0 𝑟 𝑟

𝑈 cos 𝜃 1 𝑟0 2 𝑟0 4 1 𝑟0 4 𝑟0 2 1 𝑟0 4 𝑟0 2
𝑆𝑟𝑟 + 𝑆𝜃𝜃 + 𝑆𝜙𝜙 = 3 { (( ) − ( ) ) + [( ) − ( ) ] + [( ) − ( ) ]}
𝑟0 2 𝑟 𝑟 4 𝑟 𝑟 4 𝑟 𝑟

𝑈 cos 𝜃 1 𝑟0 2 𝑟0 4 1 𝑟0 4 𝑟0 2
𝑆𝑟𝑟 + 𝑆𝜃𝜃 + 𝑆𝜙𝜙 = 3 { (( ) − ( ) ) + [( ) − ( ) ]} = 0
𝑟0 2 𝑟 𝑟 2 𝑟 𝑟

1 𝜕 𝑣𝜃 1 𝜕𝑣𝑟
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ( ) + ]
2 𝜕𝑟 𝑟 𝑟 𝜕𝜃
1 𝜕 1 1 𝑟0 3 3 𝑟0 1 𝜕 1 𝑟0 3 3 𝑟0
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ( 𝑈 sin 𝜃 [−1 + ( ) + ( )]) + (𝑈 cos 𝜃 [1 + ( ) − ( )])]
2 𝜕𝑟 𝑟 4 𝑟 4 𝑟 𝑟 𝜕𝜃 2 𝑟 2 𝑟
1 𝜕 1 1 𝑟0 3 3 𝑟0 1 1 𝑟0 3 3 𝑟0 𝜕
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟𝑈 sin 𝜃 ( [−1 + ( ) + ( )]) + 𝑈 [1 + ( ) − ( )] (cos 𝜃)]
2 𝜕𝑟 𝑟 4 𝑟 4 𝑟 𝑟 2 𝑟 2 𝑟 𝜕𝜃

1 𝜕 1 𝑟0 1 𝑟0 4 3 𝑟0 2 1 1 𝑟0 3 3 𝑟0
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟𝑈 sin 𝜃 ( [− + ( ) + ( ) ]) − 𝑈 sin 𝜃 [1 + ( ) − ( )]]
2 𝜕𝑟 𝑟0 𝑟 4 𝑟 4 𝑟 𝑟 2 𝑟 2 𝑟

1 𝑈 sin 𝜃 𝜕 𝑟0 1 𝑟0 4 3 𝑟0 2 𝑟0 1 𝑟0 4 3 𝑟0 2
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ([− + ( ) + ( ) ]) − [ + ( ) − ( ) ]]
2 𝑟0 𝜕𝑟 𝑟 4 𝑟 4 𝑟 𝑟 2 𝑟 2 𝑟

1 𝑈 sin 𝜃 1 𝑟0 2 1 𝑟0 5 3 1 𝑟0 3 𝑟0 1 𝑟0 4 3 𝑟0 2
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ([ ( ) − ( ) − ( ) ]) − [ + ( ) − ( ) ]]
2 𝑟0 𝑟0 𝑟 𝑟0 𝑟 2 𝑟0 𝑟 𝑟 2 𝑟 2 𝑟

1 𝑈 sin 𝜃 𝑟0 𝑟0 4 3 𝑟0 2 𝑟0 1 𝑟0 4 3 𝑟0 2
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [ −( ) − ( ) − − ( ) + ( ) ]
2 𝑟0 𝑟 𝑟 2 𝑟 𝑟 2 𝑟 2 𝑟

𝟑 𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟒
𝑺𝒓𝜽 = 𝑺𝜽𝒓 = − ( )
𝟒 𝒓𝟎 𝒓

1 1 𝜕𝑣𝜃 sin 𝜃 𝜕 𝑣𝜙
𝑆𝜃𝜙 = 𝑆𝜙𝜃 = [ + ( )] = 0
2 𝑟 sin 𝜃 𝜕𝜙 𝑟 𝜕𝜃 sin 𝜃

1 1 𝜕𝑣𝑟 𝜕 𝑣𝜙
𝑆𝜙𝑟 = 𝑆𝑟𝜙 = [ + 𝑟 ( )] = 0
2 𝑟 sin 𝜃 𝜕𝜙 𝜕𝑟 𝑟
𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟐 𝒓𝟎 𝟒 𝟑 𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟒
[( ) − ( ) ] − ( ) 𝟎
𝟐 𝒓𝟎 𝒓 𝒓 𝟒 𝒓𝟎 𝒓
𝟑 𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟒 𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝑺𝒊𝒋 = − ( ) [( ) − ( ) ] 𝟎
𝟒 𝒓𝟎 𝒓 𝟒 𝒓𝟎 𝒓 𝒓
𝟑 𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝟎 𝟎 [( ) − ( ) ]
[ 𝟒 𝒓𝟎 𝒓 𝒓 ]

𝒓𝟎 𝟐 𝒓𝟎 𝟒 𝟏 𝒓𝟎 𝟒
𝐜𝐨𝐬 𝜽 [( ) − ( ) ] − 𝐬𝐢𝐧 𝜽 ( ) 𝟎
𝒓 𝒓 𝟒 𝒓
𝟑𝑼 𝟏 𝒓𝟎 𝟒 𝟏 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝑺𝒊𝒋 = − 𝐬𝐢𝐧 𝜽 ( ) 𝐜𝐨𝐬 𝜽 [( ) − ( ) ] 𝟎
𝟐 𝒓𝟎 𝟐 𝒓 𝟐 𝒓 𝒓
𝟏 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝟎 𝟎 𝐜𝐨𝐬 𝜽 [( ) − ( ) ]
[ 𝟐 𝒓 𝒓 ]

2
Viscous Stress Tensor: 𝜏𝑖𝑗 = − 3 𝜇𝜕𝑘 𝑣𝑘 𝛿𝑖𝑗 + 2𝜇𝜕(𝑖 𝑣𝑗) = 2𝜇𝑆𝑖𝑗

𝒓𝟎 𝟐 𝒓𝟎 𝟒 𝟏 𝒓𝟎 𝟒
𝐜𝐨𝐬 𝜽 [( ) −( ) ] − 𝐬𝐢𝐧 𝜽 ( ) 𝟎
𝒓 𝒓 𝟒 𝒓
𝑼𝝁 𝟏 𝒓𝟎 𝟒 𝟏 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝝉𝒊𝒋 = 𝟑 − 𝐬𝐢𝐧 𝜽 ( ) 𝐜𝐨𝐬 𝜽 [( ) − ( ) ] 𝟎
𝒓𝟎 𝟐 𝒓 𝟐 𝒓 𝒓
𝟏 𝒓𝟎 𝟒 𝒓𝟎 𝟐
𝟎 𝟎 𝐜𝐨𝐬 𝜽 [( ) − ( ) ]
[ 𝟐 𝒓 𝒓 ]

P 6-3:

𝑟0 2
𝑣𝑟 = −𝑈 cos 𝜃 [1 − ( ) ] 𝑟0 2
𝑟 −𝑈 cos 𝜃 (1 − ( ) )
𝑟
𝑟0 2 𝑣𝑖 = 𝑟0 2
𝑣𝜃 = 𝑈 sin 𝜃 [1 + ( ) ] 𝑈 sin 𝜃 (1 + ( ) )
𝑟 𝑟
𝑣𝑧 = 0 [ 0 ]

From Table C.2: Cylindrical Coordinates (r, θ, z):

𝜕𝑣𝑟 1 𝜕 𝑣𝜃 1 𝜕𝑣𝑟
𝑆𝑟𝑟 = 𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ( ) + ]
𝜕𝑟 2 𝜕𝑟 𝑟 𝑟 𝜕𝜃

1 𝜕𝑣𝜃 𝑣𝑟 1 1 𝜕𝑣𝑧 𝜕𝑣𝜃


𝑆𝜃𝜃 = + 𝑆𝜃𝑧 = 𝑆𝑧𝜃 = [ + ]
𝑟 𝜕𝜃 𝑟 2 𝑟 𝜕𝜃 𝜕𝑧

𝜕𝑣𝑧 1 𝜕𝑣𝑟 𝜕𝑣𝑧


𝑆𝑧𝑧 = 𝑆𝑧𝑟 = 𝑆𝑟𝑧 = [ + ]
𝜕𝑧 2 𝜕𝑧 𝜕𝑟
𝜕𝑣𝑟 𝜕 𝑟0 2 𝜕 𝑟0 2 2 𝑟0 3
𝑆𝑟𝑟 = = {−𝑈 cos 𝜃 [1 − ( ) ]} = −𝑈 cos 𝜃 {1 − ( ) } = −𝑈 cos 𝜃 { ( ) }
𝜕𝑟 𝜕𝑟 𝑟 𝜕𝑟 𝑟 𝑟0 𝑟

𝟐𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟑
𝑺𝒓𝒓 = − ( )
𝒓𝟎 𝒓

1 𝜕𝑣𝜃 𝑣𝑟 1 𝜕 𝑟0 2 1 𝑟0 2
𝑆𝜃𝜃 = + = (𝑈 sin 𝜃 [1 + ( ) ]) + (−𝑈 cos 𝜃 [1 − ( ) ])
𝑟 𝜕𝜃 𝑟 𝑟 𝜕𝜃 𝑟 𝑟 𝑟

𝑈 𝑟0 2 𝜕 𝑈 cos 𝜃 𝑟0 2 𝑈 cos 𝜃 𝑟0 2 𝑈 cos 𝜃 𝑟0 2


𝑆𝜃𝜃 = [1 + ( ) ] (sin 𝜃) − [1 − ( ) ] = [1 + ( ) ] − [1 − ( ) ]
𝑟 𝑟 𝜕𝜃 𝑟 𝑟 𝑟 𝑟 𝑟 𝑟

𝑈 𝑟0 2 𝜕 𝑈 cos 𝜃 𝑟0 2 𝑈 cos 𝜃 𝑟0 2 𝑈 cos 𝜃 𝑟0 2


𝑆𝜃𝜃 = [1 + ( ) ] (sin 𝜃) − [1 − ( ) ] = [1 + ( ) ] − [1 − ( ) ]
𝑟 𝑟 𝜕𝜃 𝑟 𝑟 𝑟 𝑟 𝑟 𝑟

𝑈 cos 𝜃 𝑟0 2 𝑟0 2 𝑈 cos 𝜃 𝑟0 2
𝑆𝜃𝜃 = [1 + ( ) − 1 + ( ) ] = [2 ( ) ]
𝑟 𝑟 𝑟 𝑟 𝑟

𝟐𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟑
𝑺𝜽𝜽 = ( )
𝒓𝟎 𝒓

1 𝜕 𝑣𝜃 1 𝜕𝑣𝑟 1 𝜕 1 𝑟0 2 1 𝜕 𝑟0 2
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟 ( ) + ] = [𝑟 ( 𝑈 sin 𝜃 [1 + ( ) ]) + (−𝑈 cos 𝜃 [1 − ( ) ])]
2 𝜕𝑟 𝑟 𝑟 𝜕𝜃 2 𝜕𝑟 𝑟 𝑟 𝑟 𝜕𝜃 𝑟

1 𝜕 1 𝑟0 2 1 𝑟0 2 𝜕
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟𝑈 sin 𝜃 ( [1 + ( ) ]) − 𝑈 [1 − ( ) ] (cos 𝜃)]
2 𝜕𝑟 𝑟 𝑟 𝑟 𝑟 𝜕𝜃

1 𝜕 1 (𝑟0 )2 1 𝑟0 2
𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [𝑟𝑈 sin 𝜃 ([ + 3 ]) + 𝑈 [1 − ( ) ] sin 𝜃]
2 𝜕𝑟 𝑟 𝑟 𝑟 𝑟

1 1 (𝑟0 )2 1 𝑟0 2 𝑈 sin 𝜃 1 (𝑟0 )2 1 (𝑟0 )2


𝑆𝑟𝜃 = 𝑆𝜃𝑟 = 𝑈 sin 𝜃 [𝑟 (− 2 − 3 4 ) + [1 − ( ) ]] = [− − 3 3 + − 3 ]
2 𝑟 𝑟 𝑟 𝑟 2 𝑟 𝑟 𝑟 𝑟

𝑈 sin 𝜃 (𝑟0 )2 (𝑟0 )2


𝑆𝑟𝜃 = 𝑆𝜃𝑟 = [−4 3 ] = −2𝑈 sin 𝜃 [ 3 ]
2 𝑟 𝑟

𝟐𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟑
𝑺𝒓𝜽 = 𝑺𝜽𝒓 = − ( )
𝒓𝟎 𝒓

𝝏𝒗𝒛 𝟏 𝟏 𝝏𝒗𝒛 𝝏𝒗𝜽 𝟏 𝝏𝒗 𝝏𝒗𝒛


𝑺𝒛𝒛 = =𝟎 𝑺𝜽𝒛 = 𝑺𝒛𝜽 = 𝟐 [𝒓 + ]=𝟎 𝑺𝒛𝒓 = 𝑺𝒓𝒛 = 𝟐 [ 𝝏𝒛𝒓 + ]=𝟎
𝝏𝒛 𝝏𝜽 𝝏𝒛 𝝏𝒓
𝟐𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟑 𝟐𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟑
− ( ) − ( ) 𝟎
𝒓𝟎 𝒓 𝒓𝟎 𝒓 𝟐𝑼 𝒓𝟎 𝟑 − 𝐜𝐨𝐬 𝜽 − 𝐬𝐢𝐧 𝜽 𝟎
𝑺𝒊𝒋 = 𝟐𝑼 𝐬𝐢𝐧 𝜽 𝒓𝟎 𝟑 𝟐𝑼 𝐜𝐨𝐬 𝜽 𝒓𝟎 𝟑 = ( ) [ − 𝐬𝐢𝐧 𝜽 𝐜𝐨𝐬 𝜽 𝟎]
− ( ) ( ) 𝟎 𝒓𝟎 𝒓
𝒓𝟎 𝒓 𝒓𝟎 𝒓 𝟎 𝟎 𝟎
[ 𝟎 𝟎 𝟎]

2
Viscous Stress Tensor: 𝜏𝑖𝑗 = − 3 𝜇𝜕𝑘 𝑣𝑘 𝛿𝑖𝑗 + 2𝜇𝜕(𝑖 𝑣𝑗) = 2𝜇𝑆𝑖𝑗

𝟒𝝁𝑼 𝒓𝟎 𝟑 − 𝐜𝐨𝐬 𝜽 − 𝐬𝐢𝐧 𝜽 𝟎


𝝉𝒊𝒋 = ( ) [ − 𝐬𝐢𝐧 𝜽 𝐜𝐨𝐬 𝜽 𝟎]
𝒓𝟎 𝒓
𝟎 𝟎 𝟎

The viscous term in the momentum equation is: 𝜕𝑗 𝜏𝑖𝑗 = 𝛁 ∙ 𝝉

1 𝜕 1 𝜕𝜏𝑟𝜃 𝜕𝜏𝑟𝑧 𝜏𝜃𝜃 4𝜇𝑈 𝑟0 3 1 𝜕 4𝜇𝑈 𝑟0 3 cos 𝜃


(𝛁 ∙ 𝝉)𝑟 = (𝑟𝜏𝑟𝑟 ) + + − =0+ ( ) (sin 𝜃) + 0 − ( )
𝑟 𝜕𝑟 𝑟 𝜕𝜃 𝜕𝑧 𝑟 𝑟0 𝑟 𝑟 𝜕𝜃 𝑟0 𝑟 𝑟
4𝜇𝑈 𝑟0 3 cos 𝜃 4𝜇𝑈 𝑟0 3 cos 𝜃
= ( ) − ( ) =0
𝑟0 𝑟 𝑟 𝑟0 𝑟 𝑟

1 𝜕 2 1 𝜕𝜏𝜃𝜃 𝜕𝜏𝜃𝑧 𝜏𝜃𝑟 − 𝜏𝑟𝜃


(𝛁 ∙ 𝝉)𝜃 = (𝑟 𝜏𝑟𝜃 ) + + +
𝑟 2 𝜕𝑟 𝑟 𝜕𝜃 𝜕𝑧 𝑟

1 𝜕 2
4𝜇𝑈 𝑟0 3 4𝜇𝑈 𝑟0 3 1 𝜕
(𝛁 ∙ 𝝉)𝜃 = (−𝑟 ( ) sin 𝜃) + ( ) (cos 𝜃) + 0 + 0
𝑟 2 𝜕𝑟 𝑟0 𝑟 𝑟0 𝑟 𝑟 𝜕𝜃

4𝜇𝑈 1 𝜕 1 𝑟0 3 1 4𝜇𝑈 1 1 1
(𝛁 ∙ 𝝉)𝜃 = {− 2 sin 𝜃 ((𝑟0 )3 ) − ( ) sin 𝜃} = (𝑟0 )3 sin 𝜃 { 2 ( 2 ) − 4 } = 0
𝑟0 𝑟 𝜕𝑟 𝑟 𝑟 𝑟 𝑟0 𝑟 𝑟 𝑟

1 𝜕 1 𝜕𝜏𝜃𝑧 𝜕𝜏𝑧𝑧
(𝛁 ∙ 𝝉)𝑧 = (𝑟𝜏𝑟𝑧 ) + + =0+0+0=0
𝑟 𝜕𝑟 𝑟 𝜕𝜃 𝜕𝑧

Hence: 𝜕𝑗 𝜏𝑖𝑗 = 𝛁 ∙ 𝝉 = [0 0 0]𝑇 and the given flow field is inviscid.

P 6-4:

Vector Notation Index Notation Newtonian Fluid Incompressibility Condition


2
𝛁 ∙ 𝝉̿ = 𝜇𝛁 2 𝒗 𝜕𝑖 𝜏𝑖𝑗 = 𝜇𝜕𝑖 𝜕𝑖 𝑉𝑗 𝜏𝑖𝑗 = − 𝜇𝜕𝑘 𝑣𝑘 𝛿𝑖𝑗 + 2𝜇𝜕(𝑖 𝑣𝑗) 𝜕𝑖 𝑣𝑖 = 0
3

2
𝐿. 𝐻. 𝑆. = 𝜕𝑖 𝜏𝑖𝑗 = 𝜕𝑖 [− 𝜇𝜕𝑘 𝑣𝑘 𝛿𝑖𝑗 + 2𝜇𝜕(𝑖 𝑣𝑗) ] = 𝜕𝑖 [2𝜇𝜕(𝑖 𝑣𝑗) ] = 𝜇𝜕𝑖 [𝜕𝑖 𝑣𝑗 + 𝜕𝑗 𝑣𝑖 ]
3

= 𝜇[𝜕𝑖 𝜕𝑖 𝑣𝑗 + 𝜕𝑖 𝜕𝑗 𝑣𝑖 ] = 𝜇[𝜕𝑖 𝜕𝑖 𝑣𝑗 + 𝜕𝑗 𝜕𝑖 𝑣𝑖 ] = 𝜇𝜕𝑖 𝜕𝑖 𝑣𝑗 = 𝑅. 𝐻. 𝑆.


Part # 3:

Assumptions:

 Steady State flow i.e. Q1 = Q2 = Q = 0.25 m3/s


 The bend has a circular cross section
 Incompressible Fluid
 Ignore viscous effects
 Ignore the plate wall thickness
 Uniform velocity at a given cross section

0.302 0.152
Geometry: 𝐴1 = 𝜋 = 0.070686 m2 𝐴2 = 𝜋 = 0.017671 m2
4 4

Continuity:

𝑑 𝑑
𝑑𝑡
∫ 𝜌𝑑𝑉 = − ∫ 𝜌𝑛𝑗 (𝑣𝑗 − 𝑤𝑗 )𝑑𝑆 𝑑𝑡
∫ 𝑑𝑉 = − ∫ 𝑛𝑗 𝑣𝑗 𝑑𝑆

0 = −𝐴1 𝑈1 + 𝐴2 𝑈2 𝐴1 𝑈1 = 𝐴2 𝑈2 = 𝑄 = 0.25 m3/s

𝑈1 = 3.54 m/s 𝑈2 = 14.15 m/s

𝑚̇1 = 𝜌𝐴1 𝑈1 = 1000 × 0.070686 × 3.54 = 250.228 Kg/s

𝑚̇2 = 𝜌𝐴2 𝑈2 = 1000 × 0.017671 × 14.15 = 250.045 Kg/s


Mechanical Energy Equation for Incompressible, Inviscid Steady Flow with no External Work:

1 𝑝 1 𝑝
0 = − ∫ [𝜌𝑛𝑗 (𝑣𝑗 − 𝑤𝑗 ) ( 𝑣 2 + 𝑔𝑍 + )] 𝑑𝑆 = − ∫ [𝜌𝑛𝑗 𝑣𝑗 ( 𝑣 2 + 𝑔𝑍 + )] 𝑑𝑆
2 𝜌 2 𝜌

1 𝑝1 1 𝑝2
0 = −𝜌𝑈1 𝐴1 ( 𝑈12 + 𝑔𝑍1 + ) + 𝜌𝑈2 𝐴2 ( 𝑈22 + 𝑔𝑍2 + )
2 𝜌 2 𝜌

1 1
0 = − ( 𝜌𝑈12 + 𝜌𝑔𝑍1 + 𝑝1 ) + ( 𝜌𝑈22 + 𝜌𝑔𝑍2 + 𝑝2 )
2 2

1 1
𝑝2 = ( 𝜌𝑈12 + 𝜌𝑔𝑍1 + 𝑝1 ) − ( 𝜌𝑈22 + 𝜌𝑔𝑍2 )
2 2

1 1 1 1
𝑝2 = 𝑝1 + 𝜌 ( 𝑈12 + 𝑔(𝑍1 − 𝑍2 ) − 𝑈22 ) = 𝑝1 + 𝜌 ( 𝑈12 + 𝑔(𝑍1 − 𝑍2 ) − 𝑈22 )
2 2 2 2

1 1
𝑝2 = 150 + (2 3.542 + 10(0.325) − 2 14.152 ) kPa 𝑝2 = 59.675 kPa

Moment about point A (MA):

𝑀𝐴 = −0.15𝑝1 𝐴1 − 0.475𝑝2 𝐴2 + 0.2𝑊 + 0.15 𝑚̇1 𝑉1 − 0.475 𝑚̇2 𝑉2